"WINGKO SEMAR" Eksotisme Kuliner Tradisional Khas Semarang Dengan Nuansa Edukasi Budaya Wayang - Fitriah, Ida Sarotul; Helmawan, Choirul; Fitriani, Maria; Oktiviani, Fitri Nur; Basuki, Eko Anggoro Bibi (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
The agriculture result that is produced by indonesian farmers especially in java such as: pumpkin, cassava, and yams. Pumpkin, cassava, and yams have nutrient contains that useful for health. While the price are achievable so they have many potential to be developed for human food. Wingko is one of traditional meal that is the most popular in Semarang. Based on Wingkoâs extention that is never less of buyer, we have initiative to create an innovation calles âWingko Semarâto be an innovation in entrepreneurship as the way for the utilization of local food sources (Pumpkin, cassava, and yams) and as education facility about Wayang culture. Because the values of Wayang cultures that is forgot by the teenagers. The icon of Semar is choosen for this product because it can be seen by the phylosophy from Semar character. It describes a people who behaves a wise attitude. Along with the character that exists and lives forever. Based on our hope, this âWingko Semarâ bussiness can grow and develop and still exist forever. To introduce this product to the consumers, we apply marketting strategy based social promotion which promotes by using product tester so that, it can attract the consumers more effective. Besides that, we also open pre-order system not only online but also offline. The innovation of âWingko Semarâ product which is different with another product can be accepted well by public. It has a high market opportunity to be developed continously, and itâs proved by the âWingko Semarâ sale which increases every month.Keywords : Wingko ekstention, Local food sources, eduction facilities.